Literature in the Language Classroom: Roles and Pedagogy - Adhikari, Bal Ram (Journal of NELTA Gandaki, 2019)
The present article is theoretical in nature with its prime focus on the pedagogical dimension of literature in the language classroom in general and the ESL/EFL classroom in particular. It draws on some of the key publications in the field and my experience in English language education as a teacher and material developer. Moreover, I have drawn some evidence from B. Ed. and M. Ed. English courses offered to prospective teachers, and their class observation. Divided into three sections, the article begins with a checkered history of literature in mainstream language teaching methods while the second section underscores roles of literary texts in students' balanced language development. The final section proposes the pedagogical approach to and procedures of exploiting literary texts to maximize learning opportunities for students.